2D Tin Monoxide—An Unexplored p‐Type van der Waals Semiconductor: Material Characteristics and Field Effect Transistors. (12th February 2016) - Saji, Kachirayil J.; Tian, Kun; Snure, Michael; Tiwari, Ashutosh
Abstract : 2D materials are considered promising candidates for developing next‐generation high‐performance energy efficient electronic, optoelectronic, and valley‐tronic devices. Though metal oxides are widely used in the fabrication of many advanced devices, very little work has been reported on their properties in 2D limit. This article reports the discovery of a new 2D materials system, 2D tin monoxide (SnO). Layer by layer growth of SnO on sapphire and SiO2 substrates is demonstrated using a pulsed laser deposition method. The number of SnO layers is controlled by controlling the number of laser shots during the deposition process. Raman spectroscopic and X‐ray photoelectron spectroscopic analysis confirms the formation of phase pure SnO layers. Field effect transistors (FETs) using few layer SnO channels grown on SiO2 substrates are successfully fabricated. These FETs show typical p‐channel conduction with field effect mobility ranging from 0.05 to 1.9 cm 2 V −1 s −1 . Field effect mobility varies with the number of SnO layers and decreases on either sides of the optimum layer numbers (12), which is explained based on charge screening and interlayer coupling in layered materials. Abstract : A novel 2D material (2D‐SnO) and field effect transistors (FETs) are fabricated by a pulsed laser deposition technique. Layer‐by‐layer growth of SnO is observed on sapphire and SiO2 substrates. FETs are developed using few layers of SnO channel layer on SiO2 substrates. These FETs shows typical p‐channel conduction with field effect mobility ranging from 0.05 to 1.9 cm 2 V −1 s −1 .